Bebasnya Tuntutan Pencabutan Hak Politik dalam Kasus Tindak Pidana Korupsi Dihubungkan dengan Tujuan Pemidanaan - Bintang Raihan Sulaeman; Chepi Ali Firman Zakaria (UNISBA Press, 2023)
Abstract. Corruption is a crime that is very detrimental to the nation and state and can damage the morale of the nation so that corruption is grouped into extraordinary crime which requires extra action in eradicating it, so that one of the state's efforts in eradicating corruption is by imposing the maximum possible principal punishment and addition in the form of revocation of political rights. In this case, there are several questions regarding what the judge considers in making a decision in the form of revocation of political rights and what are the obstacles to law enforcement. At this writing the author uses normative juridical research methods which are carried out by examining primary and secondary legal materials. The results of the study show that the verdict does not explicitly state the existence of the revocation of political rights and should in the judge's consideration be able to see a similar case that occurred where the case against the defendant the Minister of Social Affairs Juliari Batubara was sentenced to an additional penalty for revocation of political rights, and obstacles to law enforcement for criminal acts of corruption in demands for the revocation of political rights in the official cluster is a discrepancy with the Constitutional Court Regulations which have stipulated a waiting period of 5 (five) years for convicts who carry out their decisions, which the accused should then undergo a fair or just punishment for what he has done for the delict he has committed Abstrak. Korupsi adalah suati tindak pidana yang sangat merugikan bangsa dan negara serta dapat merusak moral bangsa sehingga korupsi dikelompokan menjadi extra ordinarycrime yang membutuhkan tindakan extra pula dalam pemberantasannya, sehingga salah satu upaya negara dalam hal memberantas tindak pidana korupsi yaitu dengan menjatuhkan hukuman pokok semaksimal mungkin dan hukuman tambahan berupa pencabutan hak politik. Dalam hal ini terdapat beberapa pertanyaan mengenai apakah yang menjadi pertimbangan hakim dalam menjatuhkan putusan berupa pencabutan hak politik serta bagaimana hambatan penegak hukumnya. Pada penulisan ini penulis menggunakan metode penelitian normative yuridis yang dilakukan dengan meneliti bahan hukum primer dan sekunder. Hasil penelitian menunjukan bahwa amar putusan tidak dengan tegas menyebutkan adanya penjatuhan pencabutan hak politik serta seharusnya dalam pertimbangan hakim dapat melihat kasus serupa yang terjadi dimana kasus yang menerpa terdakwa Menteri Soasial Juliari Batubara dijatuhi hukuman tambahan akan pencabutan hak politik, dan hambatan penegakan hukum tindak pidana korupsi dalam tuntutan pencabutan hak politik dalam klaster pejabat ialah ketidaksesuaian dengan Peraturan Mahkamah Konstitusi yang sudah menetapkan rentang waktu tunggu 5 (lima) tahun kepada terpidana yang melaksanakan putusannya yang kemudian dengan seharusnya terdakwa menjalani hukuman setimpal atau adil dengan apa yang diperbuatkanya atas delict yang pernah dilakukannya.